A beam scanning Fabry–Pérot cavity antenna for millimeter‐wave applications. Issue 5 (14th October 2018) - Lan, Jianghong; Sun, Baohua; Yan, Wenbo; Mi, Mengyao
Abstract: A beam scanning Fabry‐Pérot cavity antenna (FPCA) for 28 GHz‐band is presented in this article. The proposed antenna consists of a slot‐fed patch antenna and several layers of perforated superstrates with different dielectric constant. The beam of the antenna can be controlled by moving the superstrate over the antenna. By increasing the offset between the feeding antenna and the superstrate, a larger tilt angle can be obtained. The size of the antenna is 0.95λ0 × 0.95λ0 × 0.48λ0 at 28.5 GHz. The results show the proposed antenna achieves an impedance bandwidth (S11 < ‐10 dB) of 10.5% (27.2‐30.2 GHz), and the beam can be scanned from 0° to 14° in the yoz‐plane with the offset changed from 0 mm to 2 mm. The gain of the antenna is enhanced by 5 dBi in comparison with the feeding antenna without the superstrate, which ranges from 10.91 to 11.53 dBi with the different offset. The proposed antenna is fabricated and shows a good agreement with simulated result.